Effect of growth path on the performance and carcass traits of Hereford steers finished either on pasture or in feedlot - Peripolli, Elisa [UNESP] (2018)
The objective of the present study was to evaluate the effect of nutritional management treatments during the rearing period on the performance and carcass traits of Hereford steers finished either on pasture or in feedlot. Two hundred and forty male Hereford calves, weaned at 8 months of age with an average weight of 170 +/- 17 kg, were used. After weaning, four nutritional treatments were imposed on the calves so as to obtain different daily liveweight gains (LWGs, kg/day) during the first winter (winter-growth phase). The nutritional management groups were high LWG in feedlot (HF), low LWG in feedlot (LF), high LWG on pasture (HP) and low LWG on pasture (LP). Finishing phase began when each group reached a mean liveweight (LW) of 350 +/- 28 kg. During this phase, one half of the HF, LF, HP and LP animals were finished on pasture and the other half in feedlot. The animals were slaughtered when each group attained a mean LW of 500 kg. The carcass traits ribeye area (cm(2)) and backfat thickness (mm) were measured by ultrasonography. Liveweight, LWG and ultrasonography records were analysed by repeated-measures analysis. DM intake as a percentage of LW and feed conversion ratio (FCR; kg DM/kg LW) during feedlot were analysed by ANOVA. Least-square means for LWGs of pasture-finished animals were 0.807, 0.799, 0.819c and 0.782 kg/day for HF, LF, HP and LP respectively. Least-square means for LWG of feedlot-finished animals were 1.569, 1.554, 1.484 and 1.431 kg/day for HF, LF, HP and LP respectively. Least-square means for FCR in feedlot were 7.12, 7.20, 7.97 and 8.92 for HF, LF, HP and LP respectively. Hot carcass weight had a similar trend as did LWG. Feedlot-finished animals attained heavier hot carcass weights once they received a better nutritional management during the first winter. The growth-group management did not affect (P > 0.05) dressing percentage. The carcasses of feedlot-finished animals showed higher (P < 0.05) dressing percentages than did carcasses of pasture-finished animals. Nutritional feeding management during the first winter had permanent effects on growth, carcass and FCR traits; however, the prevalence of these effects depended on the feeding system during the finishing phase. On the basis of the results obtained in the study, it is recommended that animals receive an adequate nutritional management during the first winter so as to maximise their future performance, especially for intensive beef-cattle growing-finishing systems. However, if the animals have been subjected to restriction during early growth, they should be finished under pasture conditions.